Chapter Con l'occhio di Leonardo. Città fortificate e scenari possibili: paesaggio, cartografia e architettura militare - Burgassi, Valentina (Territori, 2023)
Leonardo's interest in Vitruvian machinatio, subservient to the needs of military architecture, starts with the return of the Sienese tradition involving mechanisms used both in civil and military fields. Whilst Martini's influence on his military studies is partly known, very little is as yet known about the extent to which they were influenced by direct observation of fortified cities. This study analyses some drawings in which the Master achieves a perfect synthesis of art and science, harmonizing together the natural features of a territory and the technical aspects necessary to forge military strategies.